2022
DOI: 10.1108/ijem-11-2021-0446
|View full text |Cite
|
Sign up to set email alerts
|

The behavioural intention to use MOOCs by undergraduate students: incorporating TAM with TPB

Abstract: PurposeThe purpose of the study is to determine the impact that the crucial determinants have on the behavioural intention (BI) of undergraduates to adopt Massive Open Online Courses (MOOCs), addressing two perspectives that are students' technical experience and psychosocial factors.Design/methodology/approachThis is a questionnaire study, and all the respondents are undergraduates in Barcelona, Spain. A total of 188 students are selected as survey subjects. Data collection applies the five-point Likert scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 98 publications
2
9
0
Order By: Relevance
“…Others have confirmed that having a positive attitude towards e-learning is critical to adopting this learning method but also highlight the discomfort of experiencing new e-learning platforms, creating challenges in technology readiness (Kaushik and Agrawal, 2021). Furthermore, in a study focused on student adoption of MOOCs, authors found that perceived ease of use and behavioral intentions is explained by perceived behavioral control (Wang et al, 2022). We thus test whether feeling at ease with the collaborative technology determines students' perceptions of the learning experience and attitude toward its continued use.…”
Section: The Role Of Anxiety In Technology Acceptancementioning
confidence: 99%
See 1 more Smart Citation
“…Others have confirmed that having a positive attitude towards e-learning is critical to adopting this learning method but also highlight the discomfort of experiencing new e-learning platforms, creating challenges in technology readiness (Kaushik and Agrawal, 2021). Furthermore, in a study focused on student adoption of MOOCs, authors found that perceived ease of use and behavioral intentions is explained by perceived behavioral control (Wang et al, 2022). We thus test whether feeling at ease with the collaborative technology determines students' perceptions of the learning experience and attitude toward its continued use.…”
Section: The Role Of Anxiety In Technology Acceptancementioning
confidence: 99%
“…Innovations in education technology offer learning opportunities in various modalities, such as face-to-face, blended (hybrid) learning, online courses (Hiatt et al, 2018) and massive open online courses (MOOCs; Wang et al, 2022). Educational managers, particularly in higher education institutions, are increasingly embracing full or partial online learning as an integral part of their long-term strategy (Khandelwal et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This criterion explains how students perceive the usefulness of MOOCs in achieving their learning goals, and how easy it is to navigate the learning resources available in MOOCs. Considering that the aim of MOOCs is to make it easier for users, with the support of learning resources that are easily accessible, interesting, and important to master to increase their understanding and improve their skills, this can encourage active motivation in continuing online learning practices through MOOCs (Wang, van Hemmen and Criado, 2022).…”
Section: Behavioural Intention To Use Technologymentioning
confidence: 99%
“…Whilst research has probed into the attitude and behavioural intention of MOOCs (e.g. adoption and completion) (Wang et al, 2022), there remains a significant void in our understanding of the during and post-adoption behaviour of MOOC users. In particular, the perception and experience of learners often expose user experience gaps that service providers may overlook (Ali et al, 2022), and these are vital to the success of micro-credential programmes (Kumar et al, 2020).…”
Section: Ijem 384mentioning
confidence: 99%
“…In particular, the perception and experience of learners often expose user experience gaps that service providers may overlook (Ali et al, 2022), and these are vital to the success of micro-credential programmes (Kumar et al, 2020). Past research primarily looked into the general attributes of MOOCs, such as perceived usefulness and perceived ease of use (Wang et al, 2022), but the core attributes of MOOCs, such as programme flexibility, content quality and system quality, remain underexplored. To add, whilst MOOCs are designed with the objective of offering affordable or no-cost learning opportunities, a number of MOOC providers are struggling with the process of establishing sustainable financial models.…”
Section: Ijem 384mentioning
confidence: 99%